Vanilla andina (Vanilloideae, Orchidaceae), a new species of the membranaceous-leaved group from Peru and Ecuador - Damián, Alexander; Garzón, Henry X.; Baquero, Luis; Jiménez, Marco M.; Vélez-Abarca, Leisberth; Iturralde, Gabriel A.; Mitidieri, Nicole; Olortegui, Sergio; Cameron, Kenneth M. (Phytotaxa, 2022)
Vanilla andina, a new species belonging to subgen. Vanilla, is described and illustrated based on living material from Peru and Ecuador. The new species is similar to V. armoriquensis but can be easily distinguished by the prominent parallel callus, longitudinal narrow keels that extend above the middle of the lip and broadly obtuse to emarginate midlobe with crispate margins.